Species-specific effects of long-term microplastic exposure on the population growth of nematodes, with a focus on microplastic ingestion. (November 2020) - Mueller, Marie-Theres; Fueser, Hendrik; Höss, Sebastian; Traunspurger, Walter
Highlights: All nematode species readily ingested PS beads in a species-specific manner. MP significantly decreased the carrying capacity of Caenorhabditis elegans. MP significantly accelerated population growth of Acrobeloides nanus. Long-term multigenerational test revealed more subtle impacts of MP on C. elegans. Abstract: Microplastics (MPs; <5 mm) released into freshwaters undergo changes in their density that make them highly bioavailable to the fauna in the sediments. In fine sediments, nematodes account for up to 90% of the meiobenthic organisms and have an important position in benthic food webs, by connecting lower (bacteria) and higher (e.g., macrofauna, fish) trophic levels. Due to their high ecological relevance, ubiquitous occurrence and very high individual densities, nematodes can serve as bioindicators of environmental pollution and especially MP pollution, since the ingested microscopic particles can be easily detected in the transparent bodies of these organisms. Single-species toxicity tests with Caenorhabditis elegans have revealed dose-dependent inhibitory effects on reproduction in nematodes exposed for 96 h to relatively high concentrations of polystyrene (PS) beads. Thus, in this study, we examined whether longer-term multigenerational tests of nematodes under continuous PS bead exposure are able to reveal more subtle impacts of MPs on population growth and whether the observed effects can be linked to the species-specific life history traits of the nematodes. We therefore tested three bacterial-feeding nematode species ( C. elegans, Acrobeloides nanus, Plectus acuminatus ) by exposing them to 1.0-µm PS beads at an exposure concentration of 10 7 beads ml −1 . The experiment was conducted in semi-fluid medium for 21–49 days depending on the life-cycle characteristics of each nematode species. Ingested PS beads were quantified by fluorescence microscopy observations. Population growth rates, carrying capacities as well as doubling time and the time at which the maximum sustainable yield was reached were used to assess the effects of PS bead exposure on nematode population dynamics. All three nematode species readily ingested 1.0-µm PS beads in semi-fluid medium, but the number of ingested PS beads varied between species. PS bead exposure significantly decreased the carrying capacity of C. elegans, whereas A. nanus populations grew significantly faster in the presence of the beads. Long-term multigeneration tests revealed more subtle impacts of MP on C. elegans than occurred following short-term exposure scenarios. Our results show that MP-induced changes in nematodes population dynamics can alter nematode communities, which in term may impact the benthic food web.